Antibodies by protein engineering - Winter, Gregory (Henry Stewart Talks, 2007)
Therapeutic antibodies, Monoclonal antibodies, Rat Campath-1, IgG structure and genes, IgG antibody, Mouse-human chimeric antibodies, Humanized antibodies, Campath-1H, B-cell chronic lymphocytic leukemia (B-CLL), Multiple sclerosis, Immunogenicity of engineered antibodies, Avastin and Herceptin, The immune strategy, Generation of diversity, Humira, Human therapeutic antibodies